Exploring the psychological mechanisms of library anxiety considering achievement motivation and goal orientation - Takeda, Masaki; Suto, Satoru (Information Research an international electronic journal, 2025)
Introduction. Although library anxiety is recognised as having a negative impact on people’s exploration, its mechanisms are unknown. Moreover, no studies have systematically demonstrated the mechanisms through which exploration is modified in the context of library anxiety. This study reviewed the context and results related to library anxiety and hypothesised that achievement motives and goal orientations underlie changes in exploration. Method. A survey of approximately 2,000 participants was conducted and 642 responses were collected. Results. A covariance structure analysis of the responses revealed that, in most cases, the hope of success was significantly related to mastery goals and information seeking from all sources, with the aim of personal growth and a deeper understanding of the task. When motivated by fear of failure, participants avoid damaging their self-esteem by envisioning the event of failure or being treated lightly by others. Conclusions. These results imply that when one’s goal is to prevent the loss of self-esteem or being treated lightly by others, seeking information from other people is avoided in favour of searching for information from non-human sources.